Mencetak Kader yang Cerdas Melalui Edukasi Calistung di Desa Muara Hungi Kabupaten Hulu Sungai Tengah - Rahmadi; An'amta, Dimas Asto Aji; Mahat, Dio Kristian; Putri, Tracy Ananda; Sabrina, Siti Salma Nur; Sudrajat, Putri Yessa; Lestari, Citra Amalia; Setiawan, Muhammad Dedy; Fajriah, Syarifah; Rahima, Annisa; Mariyati, Heni (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Equitable distribution of the education curriculum still encounters obstacles that occur in Muara Hungi Village, Batang Alai Timur District, Hulu Sungai Tengah Regency. Various geographical factors and supported by the absence of a driving cadre make the quality of education in Muara Hungi Village still weak. the problem indicator is that children in grades 3 and 4 of elementary school still cannot read, therefore the PKM team launched the “CALISTUNG” (Reading, Writing and Counting) program for elementary school children in Muara Hungi Village. The PKM team seeks to accelerate the quality of student literacy through a direct interaction approach with the community to support the program that has been implemented with activities, namely: Book Donation, Calistung Education, Making Reading Corners, Educational Spectacles, competitions commemorating independence day, melamang and evaluation. The implementation of the program was carried out using the live-in method for 60 days, while the program was carried out within 33 days which took place from 29 July to 31 August 2024. The results achieved from the implementation of this program are the improvement of students' calistung skills as seen from the students' ability to read, know how to count correctly and be more skilled in writing. through these activities the PKM team also applies students must be able to teach other friends so that it is believed to be able to have a sustainable impact. In the implication, slowly Muara Hungi Village will have the quality of a generation that is smart and cares about education and is able to maintain the wisdom of the local Meratus culture.